2022
DOI: 10.3389/fneur.2022.982926
|View full text |Cite
|
Sign up to set email alerts
|

Atrial cardiopathy is associated with cerebral microbleeds in ischemic stroke patients

Abstract: ObjectiveCerebral microbleeds (CMB) are small accumulations of hemosiderin associated with cerebrovascular risk factors, but whether they are associated with atrial cardiopathy is not known. The goal of this study is to determine, among ischemic stroke patients, the association between study-defined atrial cardiopathy and CMB presence, location, and number.MethodsIschemic stroke patients admitted to Johns Hopkins (2015–2019) with transthoracic echocardiography and electrocardiography were included. Cerebral mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 42 publications
(46 reference statements)
0
3
1
Order By: Relevance
“…Patients with NCS with ACM had a significantly prospectively validating ACM's predictive value of ACM for long-term outcomes in patients with NCSs. We observed that the prevalence of ACM in our cohort was notably lower than what has been previously reported (22.2% vs. 38.3%) 19) , a difference that could be attributed to varying definitions and subtypes of stroke examined in different studies.…”
Section: Survival Analysis Of Acm In Patients With Noncardioembolic S...contrasting
confidence: 93%
See 1 more Smart Citation
“…Patients with NCS with ACM had a significantly prospectively validating ACM's predictive value of ACM for long-term outcomes in patients with NCSs. We observed that the prevalence of ACM in our cohort was notably lower than what has been previously reported (22.2% vs. 38.3%) 19) , a difference that could be attributed to varying definitions and subtypes of stroke examined in different studies.…”
Section: Survival Analysis Of Acm In Patients With Noncardioembolic S...contrasting
confidence: 93%
“…Smoking was defined as continuous smoking of at least one cigarette per day for at least six months. ACM was defined when any of the following conditions were satisfied: (1) NT-Pro BNP >250 pg/ ml 19) ; (2) PTFV1 ≥ 5,000μV•ms 20) .…”
Section: Clinical Data Collectionmentioning
confidence: 99%
“…This approach was chosen to address sparse data biases and possible separation for small sample size data in OR estimation [ 26 ]. All regression models were adjusted stepwise for potential confounders based on the literature [ 27 , 28 ]. We used SPSS version 26.0 (Chicago, IL) and R-4.3.1 for Windows (R Foundation for Statistical Computing, Vienna, Austria.…”
Section: Methodsmentioning
confidence: 99%
“…This situation can lead to unstable predictive outcomes and compromise the overall reliability of the model. When p > 0.05, the response curves of each variable at varying levels of categorical variables exhibit parallelism, which can be analyzed using an ordered logistic regression model (36,37). As a result, except for WHR and comorbidities analyzed using unordered logistic regression, all other independent variables can be analyzed using ordered logistic regression.…”
Section: Logistic Regression Analysis Of the Single Factor And Differ...mentioning
confidence: 99%